Implementasi Tata Kelola Teknologi Informasi dalam Transformasi Digital Manajemen Sumber Daya Manusia: Tinjauan Literatur - Marat Martypasha; Satria Justicio; Muhammad Hildan Afri Zakaria; Birra Sodaq Muttaqi Devari; Rifat Fachrial Farhan; Fikri Rizany Sahdana Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
In the era of rapidly accelerating digital transformation, organizational success in adopting technology for human resource management (HRM) depends not only on technological infrastructure but also on effective IT governance that bridges strategy and implementation. This study addresses the persistent execution gap between strategic HRIS/MIS/ICT adoption policies and their implementation by HR staff, caused by limited digital competencies, weak operational guidelines, and inadequate adaptive governance. It aims to identify factors influencing IT implementation effectiveness in HRM, digital competency development strategies integrated with IT governance, and governance frameworks supporting digital HRM transformation. A Systematic Literature Review (SLR) following the PRISMA 2020 protocol was conducted. From 865 articles retrieved from the ScienceDirect database, 41 studies met the eligibility criteria and were analyzed. The findings indicate that IT implementation effectiveness is shaped by four key factors: digital transformational leadership, infrastructure and data governance readiness, adaptive organizational culture, and technical-ethical risk management. Effective digital competency development combines structured reskilling/upskilling programs, AI-enabled adaptive learning, and the enhancement of AI literacy alongside uniquely human skills. Furthermore, successful digital HRM transformation requires integrating ambidextrous governance, ethical data governance, and maturity model-based roadmaps. This study proposes the IT Governance–HRM Digital Transformation Integration Framework (IGHDTIF) as a holistic conceptual model integrating these dimensions and addressing a gap identified in the reviewed literature.